Nilai Total Plate Count (TPC) pada Jajanan Pasar di Pasar Pondok Gede Kota Bekasi - Yoelianto, Yassmin Athaya; Wulan Fitriani Safari; Achamadi (Jurnal Analis Kesehatan Kendari, 2025)
Market snacks are food processed by food processors at the point of sale, whether it is sold directly or served as ready-to-eat food to the public. Market snacks can usually be found in traditional markets such as Pondok Gede Market in Bekasi City. Some of the factors that contribute to food contamination include food sources and marketing processes. This contamination can cause foodborne disesases. One of the parameters for food contamination test is Total Plate Count (TPC). The purpose of this study was to determine the TPC value of risol, dadar gulung, and lemper market snacks sold at Pondok Gede Market. The method in this study was analytic observational. The TPC test was carried out following SNI 01-2897-1992 with a modification in the diluent solution to 0.9% NaCL. The test used the pour plate method on Plate Count Agar (PCA) media incubated for 24-48 hours. The TPC value was determined by counting the number of colonies that grew on the media with dilutions of 10-1 to 10-5. The TPC value of sample 1 was 1.6 x 104 colonies/g, sample 2 was 5.1 x 107 colonies/g, sample 3 was 6 x 105 colonies/g, sample 4 was 1.1 x 104 colonies/g, sample 5 was 4.4 x 107 colonies/g and sample 6 was 1 x 106 colonies/g. The results of the study can be concluded that of the 6 samples tested, 4 samples exceeded the threshold and the other 2 samples were below the threshold set by BPOM RI No. 13 of 2019, namely with a maximum limit of 1 x 105 colonies/g for lemper samples and 5 x 104 colonies/g for dadar gulung and risol samples.